The impact of antipsychotics and benzodiazepines in the outcome of acute ischemic stroke - Diana Elisa Lopes Barros (2022)
Background and Purpose: To determine if the use of antipsychotics and benzodiazepines drugs in stroke patients correlate with unfavorable outcomes. Methods: This is a retrospective study of consecutive patients with ischemic stroke admitted to our comprehensive stroke center during 2020. Antipsychotic and benzodiazepine uses were assessed through medical records during the first 2 weeks of hospitalization. Major outcomes included modified Rankin scale (mRS) at 90 days and early neurological outcomes based on National Institute of Health Stroke Scale (NIHSS) variation. Time to discharge was calculated and it was also assessed the occurrence of adverse effects in the first 2 weeks and the recurrence of stroke, transient ischemic attack, acute myocardial infarction, or systemic embolism within 90 days. Results: Among 524 patients, the use of antipsychotics was detected in 71 patients (14%) and the use of benzodiazepines in 190 patients (36%). The use of antipsychotics and benzodiazepines was associated with a significant difference in functional independence (mRS 0-2: adjusted odds ratio (aOR)=0.35 (95% confidence interval (CI) 0.17-0.71), P<0.01 for antipsychotics; aOR=0.43 (95% CI 0.27-0.69), P<0.01 for benzodiazepines) and in mRS (ordinal shift analysis, aOR=2.16 (95% CI 1.36-3.43), P<0.01 for antipsychotics; aOR=1.93 (95% CI 1.39-2.68), P<0.01 for benzodiazepines). Patients exposed to antipsychotics had worse neurological recovery at 14 days (aOR=0.45 (95% CI 0.23-0.87), P=0.02) and higher days of hospitalization (aOR=6.87 (95% CI 1.08-12.67), P=0.02). All-cause mortality at 90 days was higher in patients exposed to benzodiazepines (aOR=2.31 (95% CI 1.24-4.27), P<0.01). No differences were found in the neurological deterioration between groups. Conclusions: Our study shows that the use of sedative and antipsychotic drugs in acute ischemic stroke is related to worse functional outcomes at 90 days. It emphasizes the recommendations to avoid these drugs and develop non-pharmacological strategies to cope with agitated patients.